NTCP polymorphisms were associated with fibrosis development in patients with chronic HBV infection - Zhenzhen Su; Bei Cai; Xiaojuan Wu; Lixin Li; Bin Wei; Liye Meng; Lu Wang; Lanlan Wang (Journal of Infection in Developing Countries)
Introduction: Sodium taurocholate cotransporting polypeptide has been identified as the hepatitis B virus (HBV) entry receptor. However, information regarding the role of sodium taurocholate cotransporting polypeptide variants in the development of HBV-related advanced cirrhosis and hepatocellular carcinoma is limited.